A new way to construct 1-singular Gelfand-Tsetlin modules - Zadunaisky, P. (Algebra and Discrete Mathematics, 2017)
We present a simplified way to construct the Gelfand-Tsetlin modules overgl(n,C) related to a 1-singular GT-tableau defined in [6]. We begin by reframing the classical construction of generic Gelfand-Tsetlin modules found in [3], showing that they form a flat family over generic points of C(n2). We then show that this family can be extended to a flat family over a variety including generic points and 1-singular points for a fixed singular pair of entries. The 1-singular modules are precisely the fibers over these points